Suppression of discontinuous precipitation and strength improvement by Sc doping in Cu-6 wt%Ag alloys. (1st February 2023) - An, Bailing; Niu, Rongmei; Xin, Yan; Starch, William L.; Xiang, Zhaolong; Su, Yifeng; Goddard, Robert E.; Lu, Jun; Siegrist, Theo M.; Wang, Engang; Han, Ke
Highlights: Sc doping significantly suppressed discontinuous Ag precipitates in Cu-Ag alloys. Sc-doping led to a 55 MPa increase in strength, with only a slight decrease in conductivity. Sc segregation at grain boundaries inhibited the nucleation of discontinuous precipitates. The UTS of Sc-doped samples was 1080 MPa, 205 MPa higher than that of non-doped samples. Abstract: In low-Ag Cu matrix alloys, the presence of coarse discontinuous precipitates may limit strength. We demonstrated that discontinuous precipitation was suppressed, and continuous precipitation was enhanced by the doping of Cu-6 wt%Ag with Sc. A high-volume fraction of continuous precipitates, which nucleated on 111 planes, led to a 55 MPa increase in strength, with only a slight decrease in electrical conductivity. The addition of Sc inhibited the nucleation of discontinuous precipitates by causing the Sc and the Ag to co-segregate onto grain boundaries, thus forming a thin intermetallic compound layer between grains. After deformation, both discontinuous and continuous precipitates were drawn into Ag fibers. The combination of deformation strain and doping caused an increase in density and a decrease in the diameter of Ag fibers, resulting in about 205 MPa increase in doped samples when the deformation strain reached 4.9. The thinner, denser Ag fibers in the doped samples also caused higher electron scattering at interfaces, leading to electrical conductivity that was 11% IACS lower than in non-doped samples. For reference, 100% IACS (International Annealed Copper Standard) is equivalent to 1.7241 μΩ cm. Graphical abstract: Image, graphical abstract